Penanaman Bibit Pohon Matoa Sebagai Upaya Peningkatan Kesadaran Lingkungan dan Pelestarian Ekosistem di Desa Sendayan - Marselius Samuel Sidabutar; Ledy Diana; Gilang Pratama Putra; Hadzira Adzakia; Hana Yosevani Gultom; Aldika Arbeta; Mhd Ihsan Anugrah; Nisa 'Ulkarimah Waldi; Nurul Qailafanny; Rio Septian Saputra; Ruth Gustina Margaretha; Zul Asfi Raihan (Unri Conference Series: Community Engagement, 2025)
This community service program by Universitas Riau's Kuliah Kerja Nyata (KKN) involved planting 300 matoa tree seedlings in Sendayan Village to raise environmental awareness, expand green areas, and support ecosystem conservation. Matoa (Pometia pinnata) was chosen for its ecological benefits as a carbon sink and economic value as a tropical fruit. The program successfully engaged the local community, students, and village officials in collaborative efforts for environmental stewardship. The planted trees are expected to contribute to improved air quality, soil preservation, and provide future economic benefits through fruit harvesting. This initiative represents a sustainable step towards improving community welfare and promoting environmental responsibility in rural Indonesia.